Soil stabilisation using Fj-Adtech method - Tawie, Rudy (Universiti Teknologi MARA, Sarawak, 2004)
As part of the MOD agreement between ZECON Engineering Bhd and UiTMCS, a team of lecturers led by Prof. Madya Dr. Azmi Ibrahim visited ZECON's Matang Road Project from 22 to 23 May 2004 to conduct a trial study to investigate the effect of soil stabilisation using a method known as FJ-ADTECH. They were also accompanied by a Technical Sales Representative of MBT (Malaysia) Sdn. Bhd., (the company that supplied the chemical admixture) and a Japanese consultant from MALJAPA Sdn. Bhd.